2013
DOI: 10.1002/ijc.28162
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy and endothelin receptor antagonists for treatment of castration‐resistant prostate cancer

Abstract: Recently, novel therapies of prostate cancer, such as immunotherapy, endothelin receptor antagonists, novel androgen receptor antagonist and novel taxanes, and others have been introduced into clinical practice. This study was performed to summarize these results of immunotherapy and endothelin receptor antagonists in the treatment of castration-resistant prostate cancer (CRPC) and derive a more precise estimation of their effect on future treatment. The PubMed database, references of published trials, and rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…These experiments revealed that osteoblasts are activated by the canine prostatic tissue through an endothelin-dependent mechanism [34]. The importance of this work is highlighted by the fact that endothelin has become an important target in human prostate cancer metastases in the last five years [35][36][37][38][39]. This particular model has the advantage of providing an easily manipulated system for investigating prostate-specific mechanisms of new bone formation.…”
Section: Dogs In Prostate Cancer Researchmentioning
confidence: 99%
“…These experiments revealed that osteoblasts are activated by the canine prostatic tissue through an endothelin-dependent mechanism [34]. The importance of this work is highlighted by the fact that endothelin has become an important target in human prostate cancer metastases in the last five years [35][36][37][38][39]. This particular model has the advantage of providing an easily manipulated system for investigating prostate-specific mechanisms of new bone formation.…”
Section: Dogs In Prostate Cancer Researchmentioning
confidence: 99%
“…There are more than 220,000 estimated new cases of PCa and over 30,000 men die from this disease per year in the United States [3]. Despite great improvement in outcomes of PCa with early-stage by early prostatespeci c antigen (PSA) testing, surgical resection and androgen deprivation therapy [4,5], the prognosis is still poor for the advanced patients, especially the emergence of castration-resistant PCa [6]. Therefore, elucidation of the molecular mechanisms underlying the initiation and progression of PCa is urgently needed to establish new therapeutic targets for PCa treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Zibotentan (ZD4054) is an oral and selective ET-A receptor antagonist in development. Atrasentan (ABT-627) is another orally bioavailable selective ET-A receptor antagonist that inhibits ET-1 activity [ 9 ]. Some randomized controlled trials (RCTs) of ET-A receptor antagonists for the treatment of CRPC are currently available, however the results of those studies have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Also the efficacy differences between zibotentan and atrasentan have not been compared. A systematic review by Shao N et al[ 9 ] comparing ET-A receptor antagonists to placebo for CRPC suggested ET-A receptor antagonists are an attractive option for such patients. However, only four studies were included in the analysis, and the comparison of ET-A receptor antagonists and docetaxel was not performed.…”
Section: Introductionmentioning
confidence: 99%